Artificial Intelligence and graduate research – The possibilities, limitations, and guardrails - Yugant Patra (Adult Education Research Conference, 2024)
Artificial Intelligence tools are evolving as important instruments in graduate-level research. This round table will discuss the use of such tools and the need to maintain the authenticity and rigor of the qualitative graduate research process.
Keywords: Artificial intelligence; graduate research; proposal development